Necessidades de Informação e Transferência de Tecnologias dos Produtores Agrários para Adaptação às Mudanças Climáticas no Distrito de Chicualacuala, Província de Gaza - Humulane A; Filimone C; Dimande, B.; Fabião A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Mozambique is considered one of the countries that will suffer significant negative effects of climate change, in particular droughts, floods and cyclones. The district of Chicualacuala, due to its geographical location, in an area with semi-arid characteristics, will suffer the consequences of cyclical droughts and floods, high temperatures and desertification. The population will be negatively affected by these phenomena, as their survival is dependent on farming and the exploitation of natural resources. On top of these factors, there is weak development of infrastructure and social services in the district. The main effects of climate change include: the reduction of agricultural productivity, loss of crops, decrease in the availability of pasture, reduction in the availability of water, higher incidences of disease and death of livestock, and land degradation. This could, therefore, lead to the reduction of household income, increased food and nutritional insecurity, and the increase in the number of cases of diseases such as malaria, cholera and diarrhea in this population.